The role of adult attachment in relationship patterns and eating attitudes - İkikardeş, Eda (İstanbul Bilgi Üniversitesi, 2015)
[Abstract Not Available]
Yetişkin bağlanma stillerinin ilişki örüntüleri ve yeme tutumları üzerindeki etkisi